2014
DOI: 10.1088/0031-8949/89/02/025601
|View full text |Cite
|
Sign up to set email alerts
|

Lattice modes in a zigzag crystal of dust particles

Abstract: A model is presented to explain the normal mode features of dust particles in a planar zigzag crystal chain for the first and second neighbors. The degrees of freedom of particles are the longitudinal and transverse displacements in plane coupled by the first and second neighbor harmonic forces in two dimensions. The constant electric force required for the electrodes to keep the zigzag structure is calculated. The coupling between transverse and longitudinal dust-lattice modes is derived. The latter is consid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…[9] There are two main types of dust waves. [10][11][12][13][14]16] One is the dust acoustic wave (DAW), which was the-oretically predicted under the weak coupling approximation (i.e., Γ < 1), but can also exist in a more strongly coupled regime Γ c ≫ Γ ≫ 1, where Γ c is the critical coupling parameter for crystallization. [10] Ruhunusiri et al [11] obtained the susceptibilities for the ions, dusts and the dust charge fluctuation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[9] There are two main types of dust waves. [10][11][12][13][14]16] One is the dust acoustic wave (DAW), which was the-oretically predicted under the weak coupling approximation (i.e., Γ < 1), but can also exist in a more strongly coupled regime Γ c ≫ Γ ≫ 1, where Γ c is the critical coupling parameter for crystallization. [10] Ruhunusiri et al [11] obtained the susceptibilities for the ions, dusts and the dust charge fluctuation.…”
mentioning
confidence: 99%
“…Homman et al [10] investigated the propagation of the DLWs in a 2D dust system in the sheath of an rf discharge. Abdikian et al [14] explained the normal-mode features of dust lattice in a planar zigzag crystal chain and showed that propagation of the longitudinal and acoustic modes depends on the distance between the two chains, and the modes may not propagate if it is too short. Murillo [6] included a static local-field correction in the description of acoustic waves in a strongly coupled dust system.…”
mentioning
confidence: 99%